Penerapan Sanksi Pidana terhadap Debitor sebagai Pelaku Tindak Pidana Pengalihan Objek Jaminan Fidusia - Husnul Khatimah; M. Syukri Akub; Marwah Marwah (UNES Law Review, 2023)
Credit payments by financial companies are certainly very beneficial for the society in fulfilling their needs. Fiduciary is one of the most popular guarantee types because it is considered easy, fast, and simple. In Indonesia, fiduciary have been regulated in Law of The Republic of Indonesia Number 42 of 1999 on Fiduciary. In general, the object of fiduciary is not allowed to be transferred by the debtor except with the agreement of the creditor or if the fiduciary object is an inventory object. But, in fact, there are still a large number of cases where the debtor transferred the fiduciary object without the agreement of the creditor. This is definitely a criminal offense as regulated in Article 36 of the Fiduciary. In imposing criminal sanctions, there are some factors that must be considered by the judges. Furthermore, decisions that have been made final legally must be executed immediately by the prosecutor. Every defendant who is sentenced to imprisonment will be placed in a Penal Institution or Detention Center to receive counseling. The research method used in this article is normative-empirical. The data used are primary, secondary, and tertiary data. All data obtained from the research results were compiled and analyzed qualitatively and described descriptively.